Selection of stain fungi on rubberwood (Hevea brasiliensis) and its growth response against chitosan - Ali Bin Abithalib Salman; LISDAR IDWAN SUDIRMAN; DODI NANDIKA (Society for Indonesian Biodiversity, 2020)
Abstract. Salman ABA, Sudirman LI, Nandika D. 2020. Selection of stain fungi on rubberwood (Hevea brasiliensis) and its growth response against chitosan. Biodiversitas 21: 4501-4508. Rubberwood (Hevea brasiliensis Muell. Arg.) is one of the most important raw materials in furniture industry in South East Asian countries, particularly in Indonesia, Thailand and Malaysia. However, due to its susceptibility to stain fungi attack, wood preservative is needed to processing this material, which has both significant cost and environmental implications. A laboratory study was conducted to identify the seasoned rubberwood attacking stain fungi and to evaluate the bioactivity of chitosan in inhibiting the stain fungi’s growth. Isolation fungi from seasoned rubberwood were obtained firstly then selection isolates were conducted in the rubberwood test samples. Isolates with the highest percentage growth on wood test samples would identify based on internal transcribed spacer (ITS) region. Chitosan were prepared in four concentration 0, 0.5, 1 and 2% (w/v). Two isolates were showed the highest percentage growth on wood test samples after six weeks, which were 90.6% for isolate code I4 and 96.2% for II4 and both isolates gained scores 5. The two isolates were identified as Aspergillus foetidus for I4 and Aspergillus aflatoxiformans for II4. Aspergillus foetidus and A. aflatoxiformans would be the newly recorded species and this is the first report about species description from rubberwood in Indonesia. The inhibition rate was increased when chitosan concentration was increased from 0 to 2%. Chitosan concentration 2% inhibited the growth of A. foetidus in 20.28%, but there is no inhibition showed on A. aflatoxiformans. The addition of chitosan in medium can increase the growth of A. aflatoxiformans and forming clear zone around the colony.